Serendipity as cultural technique. Issue 2 (3rd April 2019) - Ingraham, Chris
ABSTRACT: In a time when personalised newsfeeds and automated recommendations foreclose the exposure people have to political, cultural and social encounters outside their existing predilections, it is more important than ever to think about the ways we come across the unexpected, online and off. This essay accordingly explores the shape of serendipity in a time so bent on personalisation and findability that our techniques of discovery have attained great consequence for the affectability of that which we discover. Serendipity is typically understood as an instrument of invention: the unanticipated but fortuitous incidents that inspire a wise insight or innovation. In this view, the serendipitous is not a boon in itself, but only as it leads to something else. Such thinking, I will argue, neglects that serendipity is fundamentally a mode of encounter, and one that can be as affective and autotelic as it is cognitive and instrumental.